KEKERASAN PSIKIS, PENYEBAB, DAN DAMPAKNYA TERHADAP ANAK DALAM NOVEL GENDUK KARYA SUNDARI MARDJUKI: TINJAUAN PSIKOLOGI SASTRA - Resa Rionika; Rusdian Noor Dermawan (CARAKA, 2019)
This study aims to describe the forms of psychological violence, the causes of psychological violence, and the impact of the psychological violence in the Genduk novel. This type of research is qualitative research. Research data in the form of a unit of events contained in the paragraph Genduk novel by Sundari Mardjuki which contains information to answer the problem formulation and related to the goal. Sources of research data in the form of primary data sources, namely the novel Genduk by Sundari Mardjuki. This study uses a research instrument, the researcher itself, equipped with a set of theories about the forms of psychological violence, the causes of psychological violence, and the effects of psychological violence. Data collection techniques are done by reading the entire contents of the novel, identifying, and recording the data obtained. The data analysis technique was carried out using descriptive techniques. The results of the study are as follows. Genduk's novel psychological forms of violence are verbal violence, abuse and neglect, emotions, control, and coercion. The cause of Genduk's novel psychic violence in the form of economic factors and family factors The impact of Genduk's novel psychological violence, namely the impact of emotional disturbances and the impact of self-concept